Political Aspect as the Main Constraint to Realize Green Growth In East Kalimantan - Hartanto, Hartanto (Department of International Relations Universitas Pertamina, 2020)
The journey of economic growth and development is on an unsustainable trajectory, marked by conditions that endanger natural assets and environmental services, both of which form the basis of long-term economic growth and human well-being. Indonesia is the 6th largest emitter in the world, while East Kalimantan itself is the 6th largest emitter nationally. The fundamental question that often arises in the author's mind is